Mitos e vivências educacionais no Espaço Cultural Vila Esperança/Escola Pluricultural Odé Kayodê - Campelo Filho, Haroldo Nélio Peres (2022)
Our Thesis is based on the idea that the Myths can and have to be used in school environment. Brazil is made up of several cultures, peoples, beliefs, legends and much more. Nowadays we still have many habits that are a mix of indigenous, African and Afro-Brazilian cultures that somehow had mixed through the centuries. We strongly believe that the regular people can learn a lot of aspects of identities linked to these cultures and it can be deeply useful. Beyond that, apply the Myths as an authentic and honest formula in school would guarantee the applicability of laws 10,639/2003 and 11,645/2008 that improve the LDB, Law 9,394/1996 that determine the guidelines and bases of national education. Its goal is include in the official curriculum of the teaching network the theme of afro-brazilian and indigenous history and culture. Studying this hypothesis, we got engaged in several experiences reported in articles and dissertations exhibited mostly as art. What we propose to the entire educative network already exists for decades. We refer to the Espaço Cultural Vila Esperança and its Pluricultural School Odé Kayodê, in the city of Goiás, a place where the Myths are known to be present in an oral, written, symbolic, material, artistic, visual ways. Facing facts, not theories, we do believe that decolonial education is working out in this place. We interviewed groups of children and educators and we provided thematic questionnaires to neighbors, families and relatives, former students, the town Mayor, his staff and everyone from every place in the town. We compared the answers of each group to understand how they could be aware and satisfied about the subjects we trhew to everyone. After that, we checked the answers and separate them in categories intending to find similar points. Our aim always was that the dialogue validated the research. Decolonial studies helped us to face subjects such as racism and prejudice. To expand our thoughts on decolonial issues we made contact with the movimento latino-americano modernidade/colonialidade/decolonialidade. The movement is a great background to think about how to understand the Eurocentric believes. To understand the Iorubá and the African cultures this study aply Síkírù Sàlámì, Vansina and Hampaté Bâ. We took it as the major reference the Iorubá Orixás mitology. We did it because in our way of thinking the Iorubá culture is one of the principal bases to the philosophy, culture and religiosity of the Espaço Cultural Vila Esperança. The complete research showed that the Myths can be perfectly and successful used in the escolar environmental. Even to get interest and participation in a class room, specially the indigenous Myths, the African Myths and afrodiasporich Myths. That will be the didactic decolonization. And more. Those ones that establish a relation with this way of learn could understand better their rights and fortify their identities. We got examples that the Myths work in education can initiate with very young children and proceed helping teenagers and adults. And for sure can help teachers formation.